Pengaruh Model Conseptual Understanding Procedures Terhadap Pemahaman Konsep Matematika Peserta Didik Sekolah Dasar - Wahdaniah; Agustan Syamsuddin; Sirajuddin (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2021)
This study aims to determine the effect of the conceptual understanding procedures model on understanding mathematical concepts in fifth-grade students at Minasa Upa Elemantary School. The method used in this research is a quantitative approach with the type of research pre-experimental design with one group pretest-posttest design The sampling technique in this research is cluster random sampling. The sample in this study was VC class students, totaling 22 people. Collecting data using observation and concept understanding tests. Data analysis used descriptive statistical analysis and inferential statistical analysis. The results showed that the average learning outcomes of students' understanding of mathematical concepts before using the conceptual understanding procedures model was 57.32 in the low category and the average learning outcomes after using the conceptual understanding procedures model was 87.05 in the high category. In addition, based on the results of the normality test which states that the data is normally distributed, the data is homogeneous and the results of the hypothesis test obtained a significant value of 0.001 with a significant rate of 0.05. In addition, the results of the study are supported by the results of the t-test, while the results of t-count - 9,635 and t table -2,080 so the result states that t count > t table. Based on the results of the research above, it can be concluded that there is an effect of using the conceptual understanding procedures model on the understanding of mathematical concepts in fifth-grade students of Minasa Upa Elementary School.